2012
DOI: 10.1007/s00122-012-1793-y
|View full text |Cite
|
Sign up to set email alerts
|

Marker utility of miniature inverted-repeat transposable elements for wheat biodiversity and evolution

Abstract: Transposable elements (TEs) account for up to 80% of the wheat genome and are considered one of the main drivers of wheat genome evolution. However, the contribution of TEs to the divergence and evolution of wheat genomes is not fully understood. In this study, we have developed 55 miniature inverted-repeat transposable element (MITE) markers that are based on the presence/absence of an element, with over 60% of these 55 MITE insertions associated with wheat genes. We then applied these markers to assess genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Moreover, makers developed from IP approach have been used for various molecular breeding studies such as genetic diversity analysis, trait identification, and candidate gene analysis (Monden et al 2009;Yaakov et al 2012;. Our analysis based on the genome-specific MITE insertion showed high genetic diversity among various B. rapa accessions suggesting the importance of the MIP markers for the diversity analysis (Fig.…”
Section: Application Of Ip-bs2 Makers For Various Molecular Breeding mentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, makers developed from IP approach have been used for various molecular breeding studies such as genetic diversity analysis, trait identification, and candidate gene analysis (Monden et al 2009;Yaakov et al 2012;. Our analysis based on the genome-specific MITE insertion showed high genetic diversity among various B. rapa accessions suggesting the importance of the MIP markers for the diversity analysis (Fig.…”
Section: Application Of Ip-bs2 Makers For Various Molecular Breeding mentioning
confidence: 79%
“…DNA markers are used in a wide range of genomic and breeding applications such as construction of genetic linkage maps, genomics assisted breeding, genome-wide association studies and evolutionary studies (Purugganan and Wessler 1995;Casa et al 2000;Kwon et al 2007;Yaakov et al 2012;Varshney et al 2013). DNA markers have been developed using various methods like random amplified polymorphic DNA, restriction fragment length polymorphism, simple sequence repeats, amplified fragment length polymorphism (AFLP), sequence characterized amplified region, and single nucleotide polymorphism (Agarwal et al 2008;Kalendar et al 2011;Varshney et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Insertion polymorphism inter- and intra- Brassica species due to insertion or absence of a mTE in specific accessions was surveyed by PCR using flanking primers [48]. For MITE insertion polymorphism (MIP) analysis, 187 and 145 MITE targets were surveyed from B. rapa and B. oleracea members, respectively [30,45].…”
Section: Resultsmentioning
confidence: 99%
“…The specific distribution of these families could be considered an important evolutionary feature in the wheat genome. Furthermore, the specific distributed MITEs may be useful to develop chromosome-specific molecular markers for biodiversity and evolutionary studies (Yaakov et al, 2012;Ben-David et al, 2013). In total, 16, 17, and 17 MITE families were identified on 7A, 7B, and 7D, respectively, while the copy number of MITEs on these chromosomes was 587, 714, and 725, respectively.…”
Section: Comparative Analysis Of Mites In Wheat Group 7 Chromosomesmentioning
confidence: 99%
“…Several studies have been carried out to investigate MITEs in wheat. Yaakov et al (2012) identified some MITEs from wheat and assessed the utility of MITEs for marker development. They further systematically identified the Stowaway-like MITEs in the wheat genome using 454 survey sequences (Yaakov et al, 2013a), which provided comprehensive information about the abundance, composition, and diversity of MITEs.…”
mentioning
confidence: 99%